Non-contrast enhanced magnetic resonance imaging for characterization of Fontan associated liver disease. (15th February 2022) - Langguth, Patrick; Salehi Ravesh, Mona; Moritz, Jörg Detlev; Rinne, Katy; Harneit, Paul Lennard; Khodami, Joshua Kian; Graessner, Joachim; Uebing, Anselm; Jansen, Olav; Both, Marcus; Hansen, Jan Hinnerk
Abstract: Objectives: To evaluate the ability of non-contrast enhanced magnetic resonance imaging (MRI) techniques to characterize Fontan associated liver disease (FALD) in adolescent and adult Fontan patients. Methods: Fontan patients (n = 29) and healthy controls (n = 13) underwent an MRI protocol with T1, T2 and Apparent Diffusion Coefficient (ADC) mapping. Routine FALD screening included abdominal ultrasound and laboratory testing. Results: Median follow-up after Fontan operation was 15.1 (IQR 12.0–16.8) years. Distinct differences in tissue characteristics were visualized. T1 and T2 relaxation times were prolonged in Fontan patients, particularly of the right lobe (T1 : 745 (IQR 715–784) ms vs. 586 (IQR 555–602) ms, p < 0.001; T2 : 63 (IQR 59–64) ms vs. 58 (IQR 56–60) ms, p = 0.002). Left lobe ADC was lower in Fontan patients (1.10 (IQR 1.06–1.18) x 10 −3 mm 2 /s vs. 1.23 (IQR 1.19–1.29) x 10 −3 mm 2 /s, p < 0.001). T2 mapping was able to differentiate between controls and Fontan patients with different FALD severity. Right lobe T2 was higher in patients with moderate or severe in comparison to those with no or mild changes and healthy controls (64 (IQR 61–67) ms vs. 60 (IQR 59–63) ms vs. 58 (IQR 56–60) ms, p = 0.001). Conclusions: Non-contrast enhanced MRI methods are able to visualize regional differences in liver tissue characteristics. T1 and T2 relaxation times were prolonged in Fontan patients suggestive of fibrosis or congestive hepatopathy, while reduced ADC might reflect impaired microperfusion. These methods have promising clinical potential for detection of liver abnormalities in Fontan patients. The usefulness of T2 mapping to grade FALD severity merits further investigation. Graphical abstract: Non-contrast enhanced liver MRI in Fontan circulation Liver fibrosis is a serious morbidity in patients with Fontan circulation (Fontan associated liver disease, FALD). Fontan patients and healthy controls underwent non-contrast enhanced liver MRI with Diffusion weighted imaging and T1- and T2-mapping. Distinct differences in tissue characteristics were visualized. T1- and T2-relaxation times were prolonged in Fontan patients, particularly of the right lobe. Right lobe T2-relaxation times were higher in Fontan patients with moderate or severe FALD in comparison to healthy controls and those with no or mild FALD. T2-mapping may be a promising non-invasive screening marker to detect and grade FALD. Unlabelled Image Highlights: Reliable non-invasive methods to monitor Fontan associated liver disease have not been established. Liver tissue characterization with contrast-free magnetic resonance imaging techniques in Fontan patients and healthy controls Relaxometry and diffusion weighted imaging maps showed distinct differences between Fontan patients and healthy controls. Especially T2 -mapping has promising potential for non-invasive screening of Fontan associated liver disease.